If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(k + -4) + 8(1 + k) = 0 Reorder the terms: 3(-4 + k) + 8(1 + k) = 0 (-4 * 3 + k * 3) + 8(1 + k) = 0 (-12 + 3k) + 8(1 + k) = 0 -12 + 3k + (1 * 8 + k * 8) = 0 -12 + 3k + (8 + 8k) = 0 Reorder the terms: -12 + 8 + 3k + 8k = 0 Combine like terms: -12 + 8 = -4 -4 + 3k + 8k = 0 Combine like terms: 3k + 8k = 11k -4 + 11k = 0 Solving -4 + 11k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 11k = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 11k = 0 + 4 11k = 0 + 4 Combine like terms: 0 + 4 = 4 11k = 4 Divide each side by '11'. k = 0.3636363636 Simplifying k = 0.3636363636
| x+110=100 | | -5(x+5)=-50 | | X^2-6x-72= | | -2x+43=-5(x-8) | | 40=2w+(40-2w) | | -11+2x=-15 | | 10p+-11p=19 | | 35x+237=237 | | -3d+-48=5d | | 4x+3-2x=3x+7 | | 7+7(1+5k)= | | 10=0.5n+2.50 | | 53=-3X-7 | | -7(n-6)=56 | | (36x^2)-12=0 | | 3(w+4)=-4w-37 | | 180=64+76+x | | 11n-10n+-3n=10 | | -(6-2b)+2= | | 11(n-3)=22 | | -3d+16=5d | | -3(x-4)=-9x | | 180=45+2x+x | | K=42 | | -6(5n-3)-4=158 | | -3y-2=9y-22 | | 15-y=-5 | | y+3=5(x-5) | | 16j-15j-3j=8 | | 10-10(7+6n)= | | 6(6x-5)-6x-5=-245 | | p=8x-0.2x^2 |